Role of Descending Dopaminergic Pathways in Pain Modulation - Li, Changsheng; Liu, Sufang; Lu, Xihua; Tao, Feng (Current Neuropharmacology, 2019)
Pain, especially when chronic, is a common reason patients seek medical care and it affects the quality of life and well-being of the patients. Unfortunately, currently available therapies for chronic pain are often inadequate because the neurobiological basis of such pain is still not fully understood. Although dopamine has been known as a neurotransmitter to mediate reward and motivation, accumulating evidence has shown that dopamine systems in the brain are also involved in the central regulation of chronic pain. Most importantly, descending dopaminergic pathways play an important role in pain modulation. In this review, we discuss dopamine receptors, dopaminergic systems in the brain, and the role of descending dopaminergic pathways in the modulation of different types of pain.
Keywords: descending dopaminergic pathways